2017
DOI: 10.1002/jmrs.209
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal evaluation of early anatomical changes of parotid gland in intensity modulated radiotherapy of nasopharyngeal carcinoma patients with parapharyngeal space involvement

Abstract: IntroductionRadiotherapy of nasopharyngeal carcinoma patients with parapharyngeal space (PPS) involvement may deliver high dose to the parotid gland. This study evaluated parotid gland changes during and up to 3 months after radiotherapy.MethodsKilovoltage computed tomography (CT) scans of head and neck region of 39 nasopharyngeal carcinoma patients with PPS involvement were performed at pre‐radiotherapy, 10th, 20th and 30th fractions and 3 months after treatment. The parotid glands were contoured in pre‐radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…According to a previous report, one major advantage of using adaptive strategies is to prevent doses to the parotid glands . Some studies have reported that body weight loss is related to shrinkage of these glands, and that they shrink more as the mean dose to the gland increases . Capelle et al reported that the reduction in the diameter of the neck caused the mean dose to the parotid gland to increase .…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, one major advantage of using adaptive strategies is to prevent doses to the parotid glands . Some studies have reported that body weight loss is related to shrinkage of these glands, and that they shrink more as the mean dose to the gland increases . Capelle et al reported that the reduction in the diameter of the neck caused the mean dose to the parotid gland to increase .…”
Section: Discussionmentioning
confidence: 99%
“…In our centre, planning staff have historically placed less importance on the optimisation of the ipsilateral parotid, with the belief that once the dose exceeds tolerance, there is no substantial benefit in small improvements in dose. Zhang et al and Ren et al explain the importance of parotid sparing to negate the potential for shrinkage and medial migration of the glands during treatment increasing dose. Keeping the dose to the parotids as low as possible has been shown to have a direct impact on the development of xerostomia, functional recovery of the glands and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They were reflected by the increase of Δ%V, DSC and TVD from pre-treatment to 30 th fraction, respectively. The shrinkage of parotid glands during radiotherapy has been reported in previous studies 16,17 and it was mainly caused by the loss of gland parenchyma and acinar cell atrophy due to high dose radiation. 18,19 The volume reduction of the parotid gland subsequently changed its shape and therefore resulted in a similar trend in DSC as for Δ%V.…”
Section: Discussionmentioning
confidence: 99%